TIPOLOGI RUMAH VERNAKULAR BERDASARKAN SISTEM FISIK DI KAMPUNG BANDAR PEKANBARU, RIAU - Laili Dwi Annisa; Atiek Suprapti; Edward Edrianto Pandelaki (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2020)
The development of the city of Pekanbaru originally came from a small hamlet on the edge of the Siak river. The development of Senapelan (Kampung Bandar now) is very closely related to the development of the Sri Indrapura Siak Kingdom which brought Malay culture and architecture to Bandar Village. To learn the characteristics of an architectural building one of them can be known by studying the typology of the building. Likewise with the characteristics of houses in a settlement, this can be known by examining the typology of the houses. The purpose of this study was to determine the typology of vernacular houses based on physical elements in Kampung Bandar Pekanbaru. The typology of this house will be discussed descriptively with qualitative methods. In this study, a strategy to determine the typology of vernacular houses uses physical system parameters that will discuss typologies based on the character of the material, typologies based on space constraints and typologies based on the structure of the house. The results of the study are expected to be a foundation for maintaining and preserving vernacular houses with Malay architecture in Pekanbaru. It also can be an input for the government to be able to develop the Bandar village area by continuing to emphasize the character of Malay architecture and advanced steps such as conservation so that it can be a positive impact on the city of Pekanbaru.